2020
DOI: 10.1039/d0ma00399a
|View full text |Cite
|
Sign up to set email alerts
|

Green production of hydrogen-doped faceted cobalt microcrystals using water-assisted molten salt electro-reduction method

Abstract: We report that water can repeatedly be decomposed and regenerated in molten LiCl at 680 °C under a low cell voltage of only 1V, and these interactions lead to the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In another work, it was demonstrated that water can repeatedly be decomposed and regenerated in molten LiCl at 680 C under a low cell voltage of only 1 V, leading to the clean production and the in situ consumption of hydrogen to reduce cobalt oxide into highly faceted cobalt microcrystals with a low energy consumption of 1150 kW h per ton of reduced cobalt, providing considerable advantages over the alternative approaches available for cobalt production. 99 It was explained that the hydrogen gas generated on the cathode (reaction (9.1)) can either escape from the cathode (reaction ( 17)) or alternatively be consumed for the reduction of cobalt oxide (reaction ( 18)).…”
Section: Hydrogen Reduction Of Metal Oxides In Molten Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, it was demonstrated that water can repeatedly be decomposed and regenerated in molten LiCl at 680 C under a low cell voltage of only 1 V, leading to the clean production and the in situ consumption of hydrogen to reduce cobalt oxide into highly faceted cobalt microcrystals with a low energy consumption of 1150 kW h per ton of reduced cobalt, providing considerable advantages over the alternative approaches available for cobalt production. 99 It was explained that the hydrogen gas generated on the cathode (reaction (9.1)) can either escape from the cathode (reaction ( 17)) or alternatively be consumed for the reduction of cobalt oxide (reaction ( 18)).…”
Section: Hydrogen Reduction Of Metal Oxides In Molten Saltsmentioning
confidence: 99%
“…The cathodic and anodic potential differences were measured between the cathode/anode and a Mo pseudo-reference electrode immersed in the melt. 99 Table 1 A comparison between the molten salt hydrogen reduction of Fe 2 O 3 with the current commercial iron production methods; including energy consumption (EC, kW h per kg of Fe) and CO 2 emission (CE, ton per ton of Fe)…”
Section: Hydrogen Reduction Of Metal Oxides In Molten Saltsmentioning
confidence: 99%
“…Recently, we have introduced a new molten salt approach for metal production in which water is employed as the redox mediator. [8][9][10] It was confirmed that water introduced into the molten lithium chloride electrolyte can cause hydrolysis of the melt, and therefore, the generation of protons and oxygen anions. The protons from the electrolyte can then be discharged on the cathode under the influence of an external power source to generate hydrogen.…”
mentioning
confidence: 97%